Calibration of the GOES 13/15 high‐energy proton detectors based on the PAMELA solar energetic particle observations. Issue 9 (24th September 2017) - Bruno, A.
Abstract: The Energetic Proton, Electron, and Alpha Detector (EPEAD) and High Energy Proton and Alpha Detector (HEPAD) instruments on the Geostationary Operational Environmental Satellite (GOES) spacecraft have served over many years as monitors of the solar particle intensities, surveying the Sun and measuring in situ its effect on the near‐Earth solar‐terrestrial environment. However, the reconstruction of the differential energy spectra is affected by large uncertainties related to the poor energy resolution, the small geometrical factor, and the high contamination by out‐of‐acceptance particles. In this work, the high‐quality data set from the Payload for Antimatter Matter Exploration and Light‐nuclei Astrophysics (PAMELA) space mission is used to calibrate the high‐energy (>80 MeV) proton channels of the EPEAD and the HEPAD sensors on board the GOES 13 and 15, bringing the measured spectral intensities inline with those registered by PAMELA. Suggested corrections significantly reduce the uncertainties on the response of GOES detectors, thus improving the reliability of the spectroscopic observations of solar energetic particle events. Key Points: The high‐quality data of PAMELA are used to calibrate the high‐energy (>80 MeV) channels of the proton detectors on board of GOES 13 and 15 The effective energies of the two most energetic EPEAD channels are derived; results for both uncorrected and corrected fluxes are provided The procedure is extended to the HEPAD channels, providing the first attempt to calibrate the HEPAD sensors with space‐based observations